2016
DOI: 10.1186/s12884-015-0759-x
|View full text |Cite
|
Sign up to set email alerts
|

Gaining insight into how women conceptualize satisfaction: Western Australian women’s perception of their maternity care experiences

Abstract: BackgroundThe concept of maternal satisfaction is challenging, as women’s and clinicians’ expectations and experiences can differ. Our aim was to investigate women’s experiences of maternity care in an urban tertiary obstetric setting, to gain insight into conceptualization of satisfaction across the childbirth continuum.MethodsThis mixed method study was conducted at a public maternity hospital in Western Australia. A questionnaire was sent to 733 women two weeks post birth, which included an invitation for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 40 publications
6
39
0
1
Order By: Relevance
“…This means professionals need to improve in this field. Being well informed is very important for women; they want to be told what will happen during the birth and what is going to happen to their preterm baby . In the same way, as in other studies, the greater the feelings of control, safety, pride, and having been paid attention to by professionals, the greater the satisfaction scores …”
Section: Discussionmentioning
confidence: 79%
“…This means professionals need to improve in this field. Being well informed is very important for women; they want to be told what will happen during the birth and what is going to happen to their preterm baby . In the same way, as in other studies, the greater the feelings of control, safety, pride, and having been paid attention to by professionals, the greater the satisfaction scores …”
Section: Discussionmentioning
confidence: 79%
“…[55][56][57] The studies in this review primarily explored the adverse experiences and potential conflicts in women's IOL experiences; therefore, future research should address what constitutes a positive IOL experience and how that may be further supported by health care professionals. This is a common challenge in modern health care, which often fails to be patient-centered; however, all areas of attention identified in this review point to the importance of a communicative and patient-centered approach.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of women's satisfaction with intraand postpartum care have shown how communication and continuity of care are essential for a positive birth experience and that good communication can make up for very unfavorable situations and potentially negative experiences. [55][56][57] The studies in this review primarily explored the adverse experiences and potential conflicts in women's IOL experiences; therefore, future research should address what constitutes a positive IOL experience and how that may be further supported by health care professionals. Moreover, only one included study 36 mentioned the role of the partner.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this was the first study that assessed the Labour Agentry scores among women who experienced the care from their midwife during childbirth as “less than good.” Our finding that women with a lower sense of control during the dilation and during the pushing phase of childbirth were more likely to indicate that they experienced “less than good” midwifery care parallels the international literature about control during birth. A woman's sense of control during childbirth is internationally consistently described as a major contributing factor to a woman's childbirth experience and her subsequent well‐being .…”
Section: Discussionmentioning
confidence: 99%